THE EFFECT OF FOREIGN AND DOMESTIC INVESTMENT ON ECONOMIC GROWTH WITH THE UNEMPLOYMENT RATE AS AN INTERVENING VARIABLE - Markhamah, Siti; Mukhlis, Imam; Zagladi, Arief Noviarakhman (Nusantara Economics and Entrepreneurships Journals, 2024)
This research aims to analyze the influence of Foreign Direct Investment (FDI) and Domestic Direct Investment (DDI) on economic growth through the open unemployment rate (OUR) as an intervening variable. The research object covers Balikpapan City from 2010 to 2023. A quantitative research method is used together with the path analysis technique. The research results indicate that partially, FDI does not significantly affect the unemployment rate but has a negative and significant influence on economic growth. DDI has a negative and significant effect on the unemployment rate and a significant positive effect on economic growth. The unemployment rate has a negative and significant effect on economic growth. Based on path analysis results, the unemployment rate only successfully mediates significant influence between FDI and economic growth, but in the relationship between DDI and economic growth, it fails to mediate